2011
DOI: 10.1155/2011/906481
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tool Wear in High-Speed Milling of Hardened Powder Metallurgical Steels

Abstract: In this experimental study, the cutting performance of ball-end mills in high-speed dry-hard milling of powder metallurgical steels was investigated. The cutting performance of the milling tools was mainly evaluated in terms of cutting length, tool wear, and cutting forces. Two different types of hardened steels were machined, the cold working steel HS 4-2-4 PM (K490 Microclean/66 HRC) and the high speed steel HS 6-5-3 PM (S790 Microclean/64 HRC). The milling tests were performed at effective cutting speeds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Using these Equations, and in order to obtain Rth¼0.20 mm in both directions, the values of a p and f z used here were 0.077 and 0.079 mm, respectively, for the tools with D ¼8 mm, and 0.095 and 0.096 mm for the tools with D ¼12 mm. These values are close to those recommended by the tool supplier, which suggests depth of cut values of around 0.01D for finishing operations [37] and also close to the value used by Klocke et al [38].…”
Section: Methods Equipments and Materialssupporting
confidence: 87%
“…Using these Equations, and in order to obtain Rth¼0.20 mm in both directions, the values of a p and f z used here were 0.077 and 0.079 mm, respectively, for the tools with D ¼8 mm, and 0.095 and 0.096 mm for the tools with D ¼12 mm. These values are close to those recommended by the tool supplier, which suggests depth of cut values of around 0.01D for finishing operations [37] and also close to the value used by Klocke et al [38].…”
Section: Methods Equipments and Materialssupporting
confidence: 87%
“…Overall, tool wear was slightly decreased as the cutting speed increased from 120 m min −1 to 130 m min −1 . Klocke et al [19] demonstrated the same trend of cutting speed on tool wear, with increasing cutting speed resulting in a significant decrease in tool wear. The authors proposed that increasing the cutting speed would result in an increase in the cutting temperature at the contact zone.…”
Section: Resultsmentioning
confidence: 84%
“…By the applying a laser treatment for the tool surface is obtained a good layer hardness, thus as, the tool do not lose its working stability and to make the tool surface more resistant to action in external conditions. For the tool wear not only the hardness of the processed material has a vital role, but also the microstructure and thermal characteristics of the tool material (metallurgical powder) Klocke [3]. Under the action of the vibrations applied during welding, the material behavior is better: the density of the material deposited increases, tensions and friction of the basic material go down Luca [4].…”
Section: Introductionmentioning
confidence: 99%